Adverse pregnancy outcomes including gestational diabetes and preeclampsia: Do primary care physicians refer to them in their medical files?. (12th December 2022) - Alon, Nachshol; Tandeter, Howard; Hod, Keren; Freud, Tamar; Sheiner, Eyal
Abstract: Aims: Pregnancies complicated with gestational diabetes mellitus (GDM) or preeclampsia should be considered risk factors for subsequent morbidity later in a women's life. Appropriate screening tests have been recommended for these women. We sought to evaluate whether primary care physicians document diagnoses of GDM or preeclampsia in the medical files during the post-partum period and to elicit whether appropriate screening tests were performed. Materials and methods: The medical records of 352 women discharged from the maternity ward with a diagnosis of GDM or preeclampsia were examined 12 weeks post-partum. We recorded whether a primary care visit occurred, if a relevant diagnosis was documented and if screening tests were conducted. Results: In our cohort, 89.2% of the GDM group and 81.0% of the preeclampsia group visited a primary care physician at least once. About 12.9% ( n = 25) of the GDM group and 12.7% ( n = 20) of the preeclampsia group were given a correct diagnosis; 40.7% of the GDM group underwent a diabetes screening test and 27.8% of the preeclampsia group underwent a blood pressure measurement. Conclusion: We concluded that diagnoses of GDM and pre-eclampsia are not well-documented by primary physicians and that recommended screening tests are not being sufficiently performed.